Fetal programming of schizophrenia: Select mechanisms. (February 2015) - Debnath, Monojit; Venkatasubramanian, Ganesan; Berk, Michael
Highlights: Fetal adverse events contribute to the onset of schizophrenia in adulthood. Prenatal factors might enhance the risk of schizophrenia through inflammatory, oxidative and nitrosative stress pathways. Fetal adversity can affect brain development, brain structure and functions in schizophrenia. Abstract: Mounting evidence indicates that schizophrenia is associated with adverse intrauterine experiences. An adverse or suboptimal fetal environment can cause irreversible changes in brain that can subsequently exert long-lasting effects through resetting a diverse array of biological systems including endocrine, immune and nervous. It is evident from animal and imaging studies that subtle variations in the intrauterine environment can cause recognizable differences in brain structure and cognitive functions in the offspring. A wide variety of environmental factors may play a role in precipitating the emergent developmental dysregulation and the consequent evolution of psychiatric traits in early adulthood by inducing inflammatory, oxidative and nitrosative stress (IO&NS) pathways, mitochondrial dysfunction, apoptosis, and epigenetic dysregulation. However, the precise mechanisms behind such relationships and the specificity of the risk factors for schizophrenia remain exploratory. Considering the paucity of knowledge on fetal programming of schizophrenia, it is timely to consolidate the recent advances in the field and put forward an integrated overview of the mechanisms associated with fetal origin of schizophrenia.